2011
DOI: 10.1007/s10452-011-9385-5
|View full text |Cite
|
Sign up to set email alerts
|

Moderate acidification affects growth but not survival of 6-month-old oysters

Abstract: Oyster populations periodically exposed to runoff from acid sulfate soils (ASS) are of depressed abundance and have fewer smaller individuals than unaffected populations, despite having similar recruitment levels to unaffected sites during dry periods. We examined how the timing and duration of exposure to ASS runoff influences the growth and survival of successfully settled oysters. We predicted that among 6-month-old oysters, growth and survival would be (1) lower among individuals continuously exposed to AS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
1
19
1
Order By: Relevance
“…In some cases, estuaries are also subject to increased acid loading from acid sulphate soils (ASS). Recently, Amaral et al (2012) have reported on the impacts of a 70-day transplantation experiment to decreased pH levels (-0.8 to -1.9 pH unit) on 6-month-old oysters (Saccostrea glomerata). These juveniles appeared very resistant, as survival was not impacted by the extremely low pH levels.…”
Section: Field Studiesmentioning
confidence: 99%
“…In some cases, estuaries are also subject to increased acid loading from acid sulphate soils (ASS). Recently, Amaral et al (2012) have reported on the impacts of a 70-day transplantation experiment to decreased pH levels (-0.8 to -1.9 pH unit) on 6-month-old oysters (Saccostrea glomerata). These juveniles appeared very resistant, as survival was not impacted by the extremely low pH levels.…”
Section: Field Studiesmentioning
confidence: 99%
“…Several studies tried to understand how marine carbonateshelled animals respond to ocean acidification, such as brachiopods (McClintock et al, 2009;Cross et al, 2015Cross et al, , 2016Cross et al, , 2018Jurikova et al, 2019), bivalves (e.g. Berge et al, 2006;McClintock et al, 2009;Beniash et al, 2010;Parker et al, 2010;Melzner et al, 2011;Talmage and Gobler, 2011;Amaral et al, 2012;Hiebenthal et al, 2013;Coleman et al, 2014;Gobler et al, 2014;Milano et al, 2016), cold-water scleractinian corals (e.g. Form and Riebesell, 2011;McCulloch et al, 2012;Jantzen et al, 2013b;Büscher et al, 2017) and sea urchins (Suckling et al, 2015) (Table S1).…”
Section: Low Ph and Brachiopod Microstructurementioning
confidence: 99%
“…Over the past 10 years, accumulating evidence suggests that OA could result in delayed embryonic development [8,9], decreased larval growth [10,11] and increased mortality [12] of many marine mollusks. Moreover, OA stress has also been found to affect many physiological processes, such as calcification [13], energy metabolism [14] and behavior [15,16] of calcifying organisms.…”
Section: Introductionmentioning
confidence: 99%